Development of Arabic Language Learning Media Using the Doratoon Application in Improving Speaking Skills : Pengembangan Media Pembelajaran Bahasa Arab Menggunakan Aplikasi Doratoon dalam Meningkatkan Keterampilan Berbicara - Moh. Zulkifli Paputungan; Ceysi Yuliana Hasan; Miatin Rachmawati; M. Kholis Amrullah (Language Development Center, 2025)
Background: Arabic learning is learning that requires components as tools to help students understand the material being taught. These components are like learning media. However, at MTs al-Khairat Gorontalo City, especially grade VII, in the process of learning Arabic, learning media has not been used. Thus, students get bored quickly and the learning outcomes are not optimal. Purpose: This study aims to develop animation-based Arabic learning media using the Doratoon application to increase the learning interest of grade VII students of MTs Al-Khairat Gorontalo City. Methods: The method used is Research and Development (R&D) with the ADDIE model (analysis, design, development, implementation, and evaluation). Results and Discussion: The results of this media development show that the Doratoon application is effective in improving students' speaking skills. This is measured at a figure that reaches 93% Based on the validity test of the first two 2 validators, the calculation results show that the average score reaches 89%, which is included in the category of interpretation of the interval of 80% - 100%, with a rating of